Immigration" in the agenda's parties in Chile. Analysis of party competition (1989-2017) - Cruz, Itzel (Política. Revista de Ciencia Política, 2023)
"Immigration" has been positioned as a relevant issue in the political agendas of several countries in Latin America; however, there is a lack of systematic information on how parties have shaped this debate in the electoral arena, as well as its changes over time. This paper analyzes the dynamics of political competition around the immigration issue in Chile, covering seven elections between 1989 and 2017. Theoretically, two models that address how parties compete are taken up: the spatial model and the saliency theory; considering that together they help us explain how parties respond and try to shape political spaces. Empirically, data generated through manual coding of electoral programs is analyzed. The findings indicate that, in most of the period studied, immigration was not a polarizing issue in the electoral arena. However, this changed in 2017, an election characterized by the increase in the arrival of immigrants and the emergence of new actors in the electoral arena.